Applying the Master Narrative Framework to Gender Identity Development in Emerging Adulthood. (April 2017) - McLean, Kate C.; Shucard, Hannah; Syed, Moin
We applied a novel framework to identity development, capturing both content and process, and personal and cultural components of identity in the content domain of gender. We examined master (and alternative) narratives: ubiquitous, powerful cultural stories with which individuals negotiate in constructing personal identity. Study 1 was a quantitative investigation of personal narratives about gender ( n = 245); Study 2 was a qualitative study of discourse processes concerning gender roles ( n = 12). Employing three approaches to identity development (status, narrative, and discursive) in a mixed methods design, we found that most individuals position themselves around a newer, alternative narrative about gender equality. However, in social interactions, this narrative got less airtime, in favor of narratives representing either traditional views or gender equality. Further, those who were exploring their identities were more likely to employ the less traditional narrative, suggesting a link between changing master narratives and personal identity exploration.